VR models of death and psychedelics: an aesthetic paradigm for design beyond day-to-day phenomenology - Glowacki, David R. (Frontiers in Virtual Reality, 2024)
Near-death experiences (NDEs) and psychedelic drug experiences (YDEs) enable access to dimensions of non-ordinary sensation, perception, and insight beyond typical day-to-day phenomenology. Both are as-sociated with a dissolution of conventional spatio-temporal conceptual distinctions, and a corresponding sense of connectedness and unity which is difficult to describe. Moreover, NDEs and YDEs have shown a remarkable ability to reduce the anxiety that people associate with death. In two recent papers, we showed that multi-person virtual reality experiences (VREs) designed within the ‘numadelic’ aesthetic (where bod-ies are represented as light energy rather than material objects) can elicit psychometric results comparable to YDEs. It nevertheless remains an open question why numadelic aesthetics achieve the observed results, es-pecially given that the vast majority of VREs represent bodies as typically perceived in the ‘real-world’. This article describes the origins of the numadelic aesthetic from subjective accounts of NDE phenomenol-ogy, and attempts to unravel mechanistic aspects of the numadelic aesthetic by embedding it within a more general theoretical framework. Specifically, we elaborate a 2-axis grounded in predictive coding models of cognition and matter-energy ideas from physics. One axis tracks 'structural specificity', and the other tracks 'symbolic rigidity'. The majority of VREs, which emphasize photorealistic fidelity to content derived from 'day-to-day' phenomenology, are characterized by high structural specificity and high symbolic rigidity. Such approaches collapse imaginative potential into a limited low-entropy space of 'exogenous' possibility, unlike the high-entropy brain states associated with YDEs. In contrast, aesthetic domains characterized by low structural specificity and low symbolic rigidity are less concerned with fidelity to phenomenological priors, offering an expansive, 'uncollapsed' high-entropy possibility space for participants to engage in im-aginative meaning making and for corresponding endogenous insights (e.g., as occurs in NDEs and YDEs) to arise. Situated within this theoretical framing, the numadelic aesthetic emerges as a practical example of an un-collapsed approach to representation, helping to explain the experimental observations within previ-ous papers. Moreover, the theoretical framing suggests various experimental tests, and lays the groundwork for applying numadelic aesthetics to model NDEs, to help address the anxiety often associated with death.